Analisis Kepuasan Pelanggan Dengan Metode Servqual Dan Uji Hipotesis (Studi Kasus di PT. XYZ) - Hedi Saepudin, Tubagus (Jurnal Jaring SainTek, 2023)
This study aims to analyze and provide empirical evidence about the influence of the five variables of service quality in PT. XYZ namely reliability (X1), empathy (X2), responsiveness (X3), tangible (X4), and assurance (X5) have an effect on customer satisfaction in PT. XYZ. Data were collected by using questionnaires, data analysis technique used in this research is multiple linear regression analysis. The results of multiple linear regression analysis that has been done shows that all independent variables consisting of reliability, empathy, responsiveness, tangible, and assurance has a coefficient with a positive coefficient direction. This proves that all independent variables have a positive influence on the dependent variable of customer satisfaction. From the determinant coefficient (R2) obtained amounted to 0.969 this means 96.9% customer satisfaction is influenced by variable reliability, empathy, responsiveness, tangible, and assurance. The rest is affected by other factors that are not explained in the regression obtained in this study. Variable assurance is an independent variable that most influence on the dependent variable is 0.387.